TEACHING THE TOPIC OF RATIONAL EQUATIONS TO ACADEMIC LYCEUM STUDENTS ON THE BASIS OF NEW PEDAGOGICAL KNOWLEDGE - Ochilova , Azizabonu (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the issues of using modern pedagogical technologies to increase the effectiveness of academic lyceum students in mastering the topic of rational equations. The study highlights the role of problem-based learning, project-based approaches and ICT tools in the formation of skills in solving rational equations. Experimental work has shown that new methods develop students’ analytical thinking skills compared to traditional lessons [2,3,4,6,8].